2023
DOI: 10.1186/s13018-023-03745-1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic evaluation of the cervical spine by kinematic MRI in patients with cervical spinal cord injury without fracture and dislocation

Abstract: Background The pattern of changes in the cervical spine and the spinal cord and their dynamic characteristics in patients with cervical spinal cord injury without fracture and dislocation remain unclear. This study aimed to evaluate the dynamic changes in the cervical spine and spinal cord from C2/3 to C7/T1 in different positions by using kinematic magnetic resonance imaging in patients with cervical spinal cord injury without fracture and dislocation. This study was approved by the ethics com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…A study has shown that patients with minimal cord changes on MRI have the best outcome, followed by those with cord edema, and patients with parenchymatous hemorrhage and contusion on MRI fare poorly [19]. MRI of the latter cases frequently reveals hematomas and intramedullary edema [20].…”
Section: Discussionmentioning
confidence: 99%
“…A study has shown that patients with minimal cord changes on MRI have the best outcome, followed by those with cord edema, and patients with parenchymatous hemorrhage and contusion on MRI fare poorly [19]. MRI of the latter cases frequently reveals hematomas and intramedullary edema [20].…”
Section: Discussionmentioning
confidence: 99%